Gap-type particle acceleration in the magnetospheres of rotating supermassive black holes - Katsoulakos, Grigorios; Rieger, Frank M. (The astrophysical journal, 2020)
The detection of rapidly variable gamma-ray emission in active galactic nuclei has generated renewed interest in magnetospheric particle acceleration and emission scenarios. In order to explore its potential, we study the possibility of steady gap acceleration around the null surface of a rotating black hole magnetosphere. We employ a simpliﬁed (1D) description along with the general relativistic expression of Gauss’s law, and we assume that the gap is embedded in the radiation ﬁeld of a radiatively inefﬁcient accretion ﬂow. The model is used to derive expressions for the radial distribution of the parallel electric ﬁeld component, the electron and positron charge density, the particle Lorentz factor, and the number density of γ-ray photons. We integrate the set of equations numerically, imposing suitable boundary conditions. The results show that the existence of a steady gap solution for a relative high value of the global current is in principle possible if charge injection of both species is allowed at the boundaries. We present gap solutions for different choices of the global current and the accretion rate. When put in context, our results suggest that the variable very-high-energy γ-ray emission in M87 could be compatible with a magnetospheric origin.